2014
DOI: 10.1371/journal.ppat.1004110
|View full text |Cite
|
Sign up to set email alerts
|

Timed Action of IL-27 Protects from Immunopathology while Preserving Defense in Influenza

Abstract: Infection with influenza virus can result in massive pulmonary infiltration and potentially fatal immunopathology. Understanding the endogenous mechanisms that control immunopathology could provide a key to novel adjunct therapies for this disease. Here we show that the cytokine IL-27 plays a crucial role in protection from exaggerated inflammation during influenza virus infection. Using Il-27ra −/− mice, IL-27 was found to limit immunopathology, neutrophil accumulation, and dampened TH1 or TH17 responses via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 60 publications
6
75
0
Order By: Relevance
“…Thus, MRL/lpr mice that lack IL-27Rα have increased numbers of dermal mast cells (147), and in a model of passive cutaneous anaphylaxis, or when challenged with a helminth, Il-27rα −/− mice have elevated circulating levels of mast cell protease (12). Enhanced neutrophil activity has been a common characteristic of the absence of IL-27 in multiple experimental systems, including models of peritoneal sepsis (148) and infection with respiratory syncytial virus (RSV) (149,150); however, administering IL-27 to mice acutely infected with influenza reduced neutrophil accumulation and was associated with impaired viral clearance (20). Indeed, in mice infected with LCMV, the absence of IL-27Rα results in increased early viremia that may be due to a role of innate cells, but whether this is related to the situation seen with influenza is unclear (132).…”
Section: The Role Of Il-27 In Innate Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, MRL/lpr mice that lack IL-27Rα have increased numbers of dermal mast cells (147), and in a model of passive cutaneous anaphylaxis, or when challenged with a helminth, Il-27rα −/− mice have elevated circulating levels of mast cell protease (12). Enhanced neutrophil activity has been a common characteristic of the absence of IL-27 in multiple experimental systems, including models of peritoneal sepsis (148) and infection with respiratory syncytial virus (RSV) (149,150); however, administering IL-27 to mice acutely infected with influenza reduced neutrophil accumulation and was associated with impaired viral clearance (20). Indeed, in mice infected with LCMV, the absence of IL-27Rα results in increased early viremia that may be due to a role of innate cells, but whether this is related to the situation seen with influenza is unclear (132).…”
Section: The Role Of Il-27 In Innate Responsesmentioning
confidence: 99%
“…The discovery that WSX-1/TCCR was part of the receptor for IL-27, and that IL-27 activated STAT1 and T-bet to promote responsiveness to IL-12 and production of IFN-γ, provided a mechanism to explain how IL-27 could promote Th1 cells (1,(5)(6)(7)(8). However, when Il27ra −/− mice were challenged with different classes of viral, bacterial, or parasitic pathogens (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), or utilized in models of tissue-specific autoimmunity (24)(25)(26)(27)(28)(29)(30)(31), these experiments identified a role for IL-27 as a negative regulator of T cell responses. Since then, multiple studies have shown that IL-27 can antagonize Th1, Th2, Th9, and Th17 responses, but it has been difficult to reconcile these inhibitory activities with the ability of IL-27 to promote T cell growth and survival, and, under certain circumstances, effector T cell functions (1,32).…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of the proinflammatory response is essential to protect against tissue damage induced mortality as observed during Escherichia coli sepsis (Sewnath et al, 2001), but it is detrimental to the clearance of other bacterial infections (Auerbuch et al, 2004; Di Paolo et al, 2015; Mayer-Barber et al, 2014; McNab et al, 2014). Similarly, IL-27 protects against tissue damage during acute influenza infection (Liu et al, 2014), but compromises the host response to both secondary (Cao et al, 2014; Robinson et al, 2015) and chronic bacterial infections (Teles et al, 2015). The delicate balance between proinflammatory and anti-inflammatory responses is further illustrated by chemokine recruitment.…”
Section: Disparate Effector Mechanisms Of Type I Ifnsmentioning
confidence: 99%
“…In support of this finding, IL-27 treatment of mice in the late stage of influenza infection decreased both clinical signs of disease and lung histopathology scores without reducing clearance of the virus. 32 This improvement in pathology corresponded to significantly lower pulmonary infiltrates of both neutrophils and monocytes, which were proposed by the authors to be due to IL-27-mediated suppression of the chemokines CXCL1, CCL5, and CCL4. However, in sharp contrast to this beneficial function of IL-27, the reduction of neutrophil and monocyte infiltrates due to administration of IL-27 early in influenza infection prevented viral clearance and worsened the clinical signs of disease.…”
Section: Il-27 Activities In the Immune Systemmentioning
confidence: 70%
“…32,33 Mice with genetic deletion of IL-27Rα had more severe pulmonary histopathology and greater mortality following influenza infection than wild type mice, suggesting that IL-27 signaling is protective in influenza infection. In support of this finding, IL-27 treatment of mice in the late stage of influenza infection decreased both clinical signs of disease and lung histopathology scores without reducing clearance of the virus.…”
Section: Il-27 Activities In the Immune Systemmentioning
confidence: 99%